Low protein diet confers resistance to the inhibitory effects of interleukin1 beta on insulin secretion in pancreatic islets - Vieira, E. C.; Carneiro, E. M.; Latorraca, M. Q.; Delguingaro-Augusto, V; Amaral, MEC; Bosqueiro, JR; Boschero, A. C. (Elsevier B.V., 2001)
High protein content in the diet during childhood and adolescence has been associated to the onset insulin-dependent diabetes mellitus. We investigated the effect of interleukin-1 beta (IL-I beta) on insulin secretion, glucose metabolism, and nitrite formation by islets isolated from rats fed with normal protein (NP, 17%) or low protein (LP, 6%) after weaning. Pretreatment of islets with IL-1 beta for 1 h or 34 h inhibited the insulin secretion induced by glucose in both groups, but it was less marked in LP than in NP group. Islets from LP rats exhibited a decreased IL-1 beta -induced nitric oxide (NO) production, lower inhibition of D-[(UC)-C-14]-glucose oxidation to (CO2)-C-14, and less pronounced effect of IL-1 beta on alpha -ketoisocaproic acid-induced insulin secretion than NP islets. However, when the islets were stimulated by high concentrations of K+ the inhibitory effect of IL-1 beta on insulin secretion was not different between groups. In conclusion, protein restriction protects beta -cells of the deleterious effect of IL-1 beta, apparently, by decreasing NO production. The lower NO generation in islets from protein deprived rats may be due to increased free fatty acids oxidation and consequent alteration in Ca2+ homeostasis. (C) 2001 Elsevier B.V. All rights reserved.
Keywords: protein malnutrition; pancreatic islets; insulin secretion; interleukin 1 beta; beta cell; cytokines